Contact Simulation of Measured Surfaces with Low Roughness and Large Area Using the Elastoplastic Boundary Element Method - Tatsunori Tomota; Mamoru Tohyama; Kazuyuki Yagi (Tribology Online)
A contact between surfaces with low roughness (approximately 0.01–0.1 μm) and relatively large nominal contact area (mm2 order) is a complex phenomenon that requires consideration of deformation behavior at various scales, and is an important subject in contact mechanics. Contact simulation using the elastoplastic boundary element method is considered to be effective for this analysis. However, only a few studies have examined such contacts with a detailed comparison to measurement data, meaning that the simulation accuracy has not been sufficiently verified. Therefore, in this study, to verify their accuracy, simulations for low roughness and large area contact were performed using actual roughness shape data, and were compared with optical interferometry data of the contact surface shapes obtained in a previous study. The calculated distribution of the gap between two surfaces was similar to the measured data. Furthermore, nominal contact areas were determined from each distribution based on the statistical theory. The simulation results for nominal contact area sizes and average gaps were in good agreement with experimental results. Our findings demonstrate the utility of the elastoplastic boundary element method for the multi-scale contact analysis of surfaces with low roughness and large nominal contact area.